Development of a biomolecular approach to identify sperm functions and fertility using sperm RNAs - Pang, Won-Ki; Park, Yoo-Jin; Pang, Myung-Geol (Frontiers in Cell and Developmental Biology, 2023)
Infertility affects a significant percentage of couples worldwide, and male factors contribute significantly to this problem. Traditional assessments of male fertility rely primarily on parameters such as sperm motility, morphology, viability, and concentration. However, these metrics often do not provide a comprehensive understanding of sperm function, which is critical not only for fertilization but also for successful embryo development. Herein, we used porcine spermatozoa as a model to investigate the potential of sperm RNA markers in assessing various aspects of sperm function from motility to fertility. Using artificial insemination, we evaluated male fertility based on the litter size of sows inseminated with sperm from 20 boars. In addition, we measured parameters such as weaning rate, death births, live births, and mummy births. Sperm functional parameters, including motility and kinematics, were assessed before and after in vitro capacitation. Finally, correlations between various sperm functional parameters and sperm RNA markers were explored. Our results revealed interesting relationships between sperm functional parameters. While motility and kinematics were correlated, they were not correlated with sperm capacitation status. Surprisingly, no significant correlations were found between these parameters and male fertility. However, specific parameters of sperm capacitation status after in vitro capacitation were correlated with weaning rate and live births, highlighting their importance in predicting successful fertilization. Further analysis of sperm RNA markers identified genes related to male fertility, including IZUMO1, known for its role in sperm-egg fusion. These genes showed correlations with motility, capacitation, and fertilization parameters, shedding light on their potential roles in sperm function. In conclusion, our study demonstrates that sperm RNA markers hold promise for the diagnosis and prognosis of various aspects of sperm function, providing valuable insights into male infertility. These markers may serve as diagnostic tools to improve our understanding of male fertility problems, ultimately benefiting couples struggling with infertility.